The Role of Access Capacity of Business Actors in the “New Normal” Policy Congruence in Indonesia - Wasisto, Aryo; Lisnawati, Lisnawati (UI Scholars Hub, 2021)
In reducing the number of COVID-19 transmissions, the Government of Indonesia implemented a three-month social restriction policy. The social restriction caused shocks in the economic sector. This article analyzes the motivational factors that enable business people in Indonesia who are members of business organizations to use political party access and congruence to accelerate the